Cause and Management of Stress at Workplace: A Case of Nepalese Commercial Banks - Pradhananga, Shreeya (Nepalese Journal of Finance, 2024)
This study examines the cause and management of stress at workplace in Nepalese commercial banks. Employee turnover intention is the dependable variable. The independent variables are work ambiguity, job insecurity, work overload, work life conflict, peer relationship and work environment. The primary source of data is used to assess the opinions of the respondents regarding the cause and management of stress at workplace in Nepalese commercial banks. The study is based on primary data of 122 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing employee turnover intention in Nepalese commercial banks.The study showed that work ambiguity has a positive impact on employee turnover intention. It indicates that higher the work ambiguity, higher would be the employee turnover intention. Similarly, work life conflict a positive impact on employee turnover intention indicating that increase in work life conflicts leads to increase in employee turnover intention. Likewise, job insecurity has a positive impact on employee turnover intention. This implies that higher the job insecurity, higher would be the employee turnover intention. Similarly, work overload has a positive impact on employee turnover intention. This revels that increase in work overload leads to increase in employee turnover intention. However, peer relationship has a negative impact on employee turnover intention indicating that healthy relationship among the colleagues leads to decrease in employee turnover intention. Moreover, working environment has a negative impact on employee turnover intention indicating that supportive working environment leads to decrease in employee turnover intention.